Examining the role of sociodemographic characteristics and smartphone usage patterns on smartphone addiction among foundation program students using multiple regression analysis - Dg Siti Nurisya Sahirah Ag Isha; Nurliyana Juhan; Mohammad Zahirul Hoque; Yong Zulina Zubairi; Abu Sayed Md. Al Mamun (Penerbit Akademi Baru, 2025)
Smartphones have become an integral part of daily life, especially among young adults who depend on them for communication, entertainment, education, and social interaction. Despite their benefits, growing concerns have emerged regarding excessive and potentially harmful smartphone use, leading to smartphone addiction. These concerns highlight the urgent need to understand the factors contributing to this issue. This study adopts a cross-sectional design to investigate the influence of sociodemographic characteristics and smartphone usage patterns on smartphone addiction. The research involves 404 randomly selected students from the Foundation Program at Universiti Malaysia Sabah. Data are analyzed using Chi-square test, t-test, ANOVA, and multiple regression analysis with SPSS software. The results reveal that 43.3% of the students were classified as addicted to smartphones. Five key factors are identified to significantly contribute to smartphone addiction, namely gender, purpose of use, self-evaluation of addiction, latest time of use, and duration of use before stopping to sleep. These findings can support the development of evidence-based intervention and preventive strategies targeted at young adults. It also offers valuable insights for mental health professionals, educators, and policymakers aiming to promote healthier smartphone habits within this vulnerable population.